Aquaflo / Mohamad Muizzuddin Mohamad Nurul Azmi - Mohamad Nurul Azmi, Mohamad Muizzuddin (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2024)
AQUAFLO is an aquaponic kit designed for coffee shops, aiming to naturally bring greenery into hallways with minimal maintenance. This innovative design focuses on both style and practicality, ensuring simplicity for easy handling. Unlike traditional plant containers that demand space and intricate usage, AQUAFLO addresses these challenges with a userfriendly and visually to increase visibility coffee shop surrounding. The product represents a shift towards modern urban greenery, visualizing a harmonious blend of nature within coffee shop settings. AQUAFLO is designed to overcome limitations seen in existing hallway setups, providing a streamlined, space-efficient, and visually enriching aquaponic experience. By merging sustainability and aesthetics, it caters to the preferences of coffee shop patrons and staff alike. AQUAFLO's approach promises to redefine the presence of greenery in urban spaces, making it accessible and enjoyable for everyone involved. With its contemporary and practical design, AQUAFLO sets out to revolutionize indoor plant cultivation in coffee shop environments, offering a fresh and visually pleasing solution.